TVER STATE UNIVERSITY: CREATING THE FUTURE - I. A. KAPLUNOV; A. A. MALTSEVA (Высшее образование в России)
The paper addresses the problem of positioning regional universities in the socio-economic system of the Russian Federation. The authors dwell on the current trends in the development of Russian higher education, supported at the state level. On the example of the Tver region the paper shows that the allocation of a strong university in the region has obvious competitive advantages and creates the basis for its faster growth. Large universities that integrate a wide range of training and educational programs and able to concentrate scientific and research potential on their territory can become serious “players” on the stage of innovative development of the country. The university’s fundamental and applied research is becoming the driving force of intellectual resource and the innovation process development. The authors focus on the mechanisms for achieving strategic goals on the basis of networking cooperation and integration of educational, scientific and innovative activities.